Fast Public-Key Cryptosystems: Design And Cryptanalyses - Go, Bok Min (2006)
This research is about the design and cryptanalysis of fast public key cryptosystems.This thesis also presented a detailed study on the standard block cipher modes of operations and showed how to exploit their special properties/weaknesses to attack public-key-based security protocols.